Aesthetic rejuvenation challenges and solutions a world perspective - Carniol, Paul J.; Monheit, Gary D. (Series in cosmetic and laser therapy., 2010)
This book looks at those complicated areas that tend to be ignored in the more standard textbooks, but are of intense interest to those practitioners who are confronted by a patient not conforming to the standard treatment; it pools the expertise of top aesthetic practitioners to help point out the areas of special challenge that arise in clinical practice and how to set about tackling and solving them.